Study on the Evaluation of Lung Cancer Patients from the Three Aspects of Emotion. (15th September 2022) - Li, Panpan; Yu, Jiangli; Wang, Xiaohui; Pang, Xiaonan; Yu, Chengjing; Xu, Yingqiong
Abstract : In recent years, epidemiological survey data have shown that lung cancer is the tumor with the fastest increase in cancer incidence and mortality in China. The incidence and mortality of lung cancer in China rank first among tumors, and 80% of patients die within one year of diagnosis. This paper aims to study the evaluation of lung cancer patients from three aspects of emotion, coping style, and Quality of Life (QoL), expounding on the changes in emotion, coping style, and QoL in lung cancer patients after chemotherapy. We assess the negative emotions and survival of lung cancer patients after chemotherapy quality satisfaction survey research. We investigate the general data, QoL, and coping styles of 219 lung cancer patients undergoing chemotherapy before, during, and after chemotherapy based on the artificial intelligence processor. All survey data are input into SPSS 19 for descriptive and relevant statistical analysis. The experimental results show that under a survey of 219 lung cancer chemotherapy patients with negative emotions and QoL satisfaction after chemotherapy, at a significance level of = 0.05, there is a linear regression relationship between mental resilience and anxiety and depression.